Long-term outcomes of intravitreal injection of bevacizumab for choroidal neovascularization associated with choroidal osteoma - Yoshikawa T (Dove Medical Press, 2015)
Tadanobu Yoshikawa, Kanji Takahashi Department of Ophthalmology, Kansai Medical University, Osaka, Japan Purpose: To describe the outcomes of intravitreal injections of bevacizumab for choroidal neovascularization (CNV) associated with choroidal osteoma. Methods: Retrospective consecutive case series. Three eyes of three patients were studied. All patients were treated with intravitreal injections of bevacizumab for CNV associated with choroidal osteoma. Best-corrected visual acuity, central foveal thickness, tumor thickness on spectral domain optical coherence tomography, and subretinal pigmentation around the CNV were evaluated. Results: The mean number of intravitreal injections of bevacizumab was 2.0 (range 1–3). The mean follow-up time was 56.0 months (range 25–99 months). The mean LogMAR visual acuity worsened from 0.1 to 0.6. LogMAR visual acuity loss of 0.7 or worse occurred in two of three eyes. CNV was located in the subfoveal area in two eyes, and CNV was located in the juxtafoveal area in one eye. The mean central foveal thickness decreased from 407 µm to 251 µm. The mean tumor thickness decreased from 709 µm to 608 µm. All eyes had subretinal pigmentation around the CNV. Conclusion: Intravitreal injections of bevacizumab for subfoveal CNV associated with decalcified choroidal osteoma resulted in poor visual acuity. Keywords: choroidal osteoma, choroidal neovascularization, bevacizumab, Avastin, vascular endothelial growth factor